QAUL QADIM DAN QAUL JADID ASY-SYAFI’I: (Tinjauan Sejarah dan Sosiologi Hukum Islam) - Herdiansyah; M. Hasbi Umar; Ramlah (Indra Institute Research & Publication, 2023)
This research is a type of library research, by examining sources from books and literature related to the issues discussed, or other supporting sources. With the focal point of Imam Shafi'i's Ijtihad, known as qaul qadim and qaul jadid in a review of the history and sociology of Islamic law. The conclusion in this study is that the two styles of Imam Syafi'i's ijtihad, both qaul qadim and qaul Jadid, according to some contemporary researchers, conclude that social condition factors have an influence on Islamic legal considerations contained in the fatwa resulting from a different ijtihad or a change in fatwa caused by considerations of reality. Social studies show that the determination of Imam Shafi'i's law is very sociological. Although this assumption is not agreed upon by some researchers. They denied that the different environmental conditions between Iraq and Egypt were not the cause of the emergence of qaul jadid, but that the difference in fatwas was partly due to Imam Syafi'i's growing knowledge with the discovery of hadiths that he had not previously encountered. Although they do not deny that social factors in society can influence the outcome of an ijtihad if it is related to the field of muamalah which is based on zhanni arguments such as masalahah or urf. But not in the field of worship which is based on qath'i. texts.